Cereblon pathway biomarkers and immune profiles in patients with myeloma receiving post-ASCT lenalidomide maintenance (LEOPARD). Issue 12 (15th October 2021) - Kalff, Anna; Khong, Tiffany; Ramachandran, Malarmathy; Walker, Patricia; Schwarer, Anthony; Roberts, Andrew W.; Campbell, Philip; Filshie, Robin; Norton, Sam; Reynolds, John; Young, Mary; Pierceall, William; et al.
Abstract: LEOPARD was a single arm, phase II study of lenalidomide (LEN) and alternate day prednisolone maintenance in patients with newly diagnosed multiple myeloma (MM) following autologous stem cell transplantation (ASCT). Sixty patients were enrolled. Estimated median potential follow-up was 44 m, median PFS was 38.3 m, median OS was not reached (landmark 36 m OS: 71.4%). Correlative immunohistochemistry performed on pre-ASCT trephines demonstrated high MM tumor cereblon (total/cytoplasmic) was associated with superior OS ( p = .045, p = .031, respectively), whereas high c-Myc was associated with inferior PFS ( p = .04). Patients with high cereblon (total/nuclear) were more likely to improve depth of response, whereas patients with high c-Myc were less likely, suggesting alternative/more effective post-ASCT strategies for patients with high c-Myc need identification. Peripheral blood immune profiling (mass cytometry) informed a more sustained response to LEN maintenance, demonstrating enrichment of activated/cytotoxic NK cells and cytotoxic T cells in patients with durable responses, contrasting with enrichment of B-regs in early relapsers.